UTILIZATION OF SOYBEAN POWDER AS AN ALTERNATIVE MEDIA FOR THE GROWTH OF ANAEROBIC BACTERIA - Aisha Nafa Firdausi; Aminah Aminah; Indra Setyawati (Dentino: Jurnal Kedokteran Gigi, 2024)
Background:Culture media or microbial growth media is a material consisting of a mixture of nutrients used by microorganisms for growth and reproduction. Anaerobic bacteria can thrive by requiring little or no oxygen for growth and metabolism. Purpose: The purpose to determine the potential of soybean powder as an alternative nitrogen source in Streptococcus mutans bacterial growth media and determine the optimum concentration of soybean powder in alternative media for Streptococcus mutans bacterial growth. Methods: The research method is a laboratory experiment to test soybean powder as an alternative medium for the growth of Streptococcus mutans bacteria using the Candle jar method. The population used is soybean powder with the brand soy flour, while the sample used is Streptococcus mutans bacteria. Results: The results obtained can be known that the average value of colony growth of Streptococcus mutans bacteria in alternative media of soybean powder with a concentration variation of 2 grams was 30 colonies, a concentration variation of 3 grams was 54 colonies, a concentration variation of 4 grams was 40 colonies, and a concentration variation of 5 grams was 72 colonies. From the average value, it can be seen that the growth of Streptococcus mutans on alternative media of soybean powder can grow well, but the most optimum growth is in the concentration variation of 5 grams. Conclusion:Based on the observations obtained, it shows that soybean powder (Glycine max (L.) Merr) can be used as an alternative medium for the growth of Streptococcus mutans bacteria.